ANALISIS YURIDIS PANITIA SELEKSI DEWAN PENGAWAS KOMISI PEMBERANTASAN KORUPSI BERDASARKAN UNDANG – UNDANG REPUBLIK INDONESIA NOMOR 19 TAHUN 2019 TENTANG PERUBAHAN KEDUA ATAS UNDANG–UNDANG NOMOR 30 TAHUN 2002 TENTANG KOMISI PEMBERANTASAN TINDAK PIDANA KORUPSI - Nasution, Hary Doly; Firdaus, Emilda; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
This research analyzes juridically the regulation and ideal criteria of theSelection Committee for the Supervisory Board of the Corruption EradicationCommission (KPK) based on Law Number 19 of 2019 concerning the SecondAmendment to Law Number 30 of 2002 concerning the KPK. The existence of theKPK Supervisory Board has been met with pros and cons because it is consideredto be able to affect the independence of the anti-corruption institution. Theformation of the Supervisory Board is feared to actually erode the authority andinternal supervisory function of the KPK and disrupt the corruption eradicationprocess.This research is a normative legal research with a qualitative approachthat examines secondary data in the form of primary and secondary legalmaterials. Primary data is obtained from relevant laws and regulations such asLaw Number 19 of 2019 and its derivative regulations, while secondary data isfrom legal literature such as books, scientific journals, research results, andscientific articles. The thinking method used is the deductive method to drawconclusions from general statements to specific ones, and inductive to concludefrom specific matters to general ones.This research analyzes juridically the regulation of the SelectionCommittee for the Supervisory Board of the Corruption Eradication Commission(KPK) based on Law Number 19 of 2019 concerning the Second Amendment toLaw Number 30 of 2002 and examines the ideal criteria for the selectioncommittee.. Therefore, it is necessary to have detailed regulations regarding theideal criteria for the selection committee from the government and communityelements so that its implementation can maintain the integrity and independenceof the KPK in accordance with the principles of the formation of the anti-corruption institutionKeywords : Corruption Eradication Commission, Supervisory Board, SelectionCommittee.